More than an Incidentaloma: The Nonreportable NIPT. (30th April 2022) - Jay, Allison M.; Mason, Brian; Lebovic, Daniel; Chuba, Paul
Abstract : Noninvasive prenatal testing (NIPT), which utilizes a maternal blood sample to detect fetal gender and screen for fetal aneuploidy (abnormal chromosomes), is widely used in obstetrics to screen for Trisomies 21, 18, and 13. Per the literature, approximately 0.3% of pregnant woman's results are nonreportable. Reasons include low fetal fraction, insufficient DNA, vanishing twin, twin pregnancy, clonal mosaicism, and maternal neoplasia. Here, we describe a 25-year-old G2P1 pregnant woman who had two nonreportable NIPT results and subsequently was diagnosed with lymphoma. We discuss the importance of clinical exam in correlation with the results to offer comprehensive evaluation of the patient with a nonreportable finding, given malignancy occurs in 1/1000 pregnant women. This report overviews proposed management guidelines for pregnant women with a nonreportable result and helps to address discomfort the treating physician may feel in discussing this result with their patient.